(untitled) (International Journal of Engineering and Computer Science, 2014)
Image processing is a method to convert an image into digital form and perform some operations on it, in order to get an enhanced image or to extract some useful information from it. Image processing usually refers to digital image processing, but optical and analog image processing also are possible. This article is about general techniques that apply to all of them. The acquisition of images (producing the input image in the first place) is referred to as imaging. Image segmentation is a process of partitioning an image into sets of segments to change the representation of an image into something that is more meaningful and easier to analyze.